(untitled) (Medical Forum Monthly, 2022)
Objective: The rationale of our study is to find out the risk factors of developing in patients suffering from endometrial hyperplasia so that patients may be detected early and saved from developing cancer. Study Design: cross sectional study Place and Duration of Study: This study was conducted at the Department of Gyn & Obs at PMCH Nawabshah from January 2019 to December 2020 for a period of one-year. Materials and Methods: Total patients included in this were 91. All the patients aged >40 to 65 years with any parity having complain of vaginal bleeding. Patients having uterine fibroids were excluded from the study. Detailed history regarding age, gravid parity and bleeding were taken apart from thorough clinical examination. Transvaginal sonography was performed using vaginal transducer of 6.5 MHz frequency. Endometrium hyperplasia was labeled as in the form of present or absent. If hyperplasia is found, endometrial tissue was taken to see its conversion into carcinoma through D&C. Results: Total patients included in this study were 91. Of them 65 (71%) were nulliparous and 26 (29%) were multiparous. It ranged between 40 to 65 years with mean age of 48 years. 35 (38.5%) patients were of age40 to 50 years. 30 (33%) patients were aged from 51 to 55 years. 26 (28.5%) patients age was from 56 to 65 years. Only 20 (22%) patients were diagnosed as endometrial carcinoma on histopathology. Of 20, only 5 (22.7%) patients had simple hyperplasia and 15 (68%) had complex hyperplasia. Conclusion: It is concluded that null parity is the most significant risk factor in our study and prevalence of EC is decreased in our study.